Metro bus transit frequency regulation system for a smart city using an optimization algorithm - S.Govindaraj, S.; Dhalia Sweetlin, J.; Vignesh, A.; Daphy Louis Lovenia, J.; Roshini, C.; Horsley Solomon, P. (International Journal of Engineering and Technology, 2019)
Background:The increase in passengers with inadequate number of buses available results in an overcrowded bus. This is accompanied by a cramped experience for the passengers.Objectives:To facilitate the passengers and to ease their travel, by automating bus and route allocation.Methods:In this work, a Metro Bus Transit Frequency Regulation System Using Nelder-Mead Optimization Algorithm is presented. This system allows the Metropolitan Transport Corporation to allot buses in specified routes according to the demands and eases the ordeal that daily commuters face. Additionally, it aims to reduce the fuel expenses incurred by the Metropolitan Transport Corporation by optimizing the allocation of the number of buses in a particular route. It not only assuages the distresses of the passengers but also looks to reduce the woes of the workers of the Transport Corporation in allocation of buses. The vision of the proposed work is to produce a smart automated bus transit system which paves the way for a technologically improved city.Results:The simulation of the system resulted in 95% of requirements satisfaction by the passengers by using an average resource of 70% during the peak hours in the morning.Conclusions: From the results, it is inferred that developing a transit frequency regulation system will definitely ease the commutation of passengers and also reduces the fuel expenses. Indirectly the system can be used to reduce air pollution by reducing the number of private vehicles on road.Â Â